Saturation-recovery myocardial T 1 -mapping during systole: accurate and robust quantification in the presence of arrhythmia - Meßner, Nadja; Budjan, Johannes; Loßnitzer, Dirk; Papavassiliu, Theano; Schad, Lothar R.; Weingärtner, Sebastian; Zöllner, Frank G. (Scientific reports, 2018)
Myocardial T1-mapping, a cardiac magnetic resonance imaging technique, facilitates a quantitative measure of fibrosis which is linked to numerous cardiovascular symptoms. To overcome the problems of common techniques, including lack of accuracy and robustness against partial-voluming and heart-rate variability, we introduce a systolic saturation-recovery T1-mapping method. The Saturation-Pulse Prepared Heart-rate independent Inversion-Recovery (SAPPHIRE) T1-mapping method was modified to enable imaging during systole. Phantom measurements were used to evaluate the insensitivity of systolic T1-mapping towards heart-rate variability. In-vivo feasibility and accuracy were demonstrated in ten healthy volunteers with native and post-contrast T1-mappping during systole and diastole. To show benefits in the presence of RR-variability, six arrhythmic patients underwent native T1-mapping. Resulting systolic SAPPHIRE T1-values showed no dependence on arrhythmia in phantom (CoV < 1%). In-vivo, significantly lower T1 (1563 ± 56 ms, precision: 84.8 ms) and ECV-values (0.20 ± 0.03) than during diastole (T1 = 1580 ± 62 ms, p = 0.0124; precision: 60.2 ms, p = 0.03; ECV = 0.21 ± 0.03, p = 0.0098) were measured, with a strong correlation of systolic and diastolic T1 (r = 0.89). In patients, mis-triggering-induced motion caused significant imaging artifacts in diastolic T1-maps, whereas systolic T1-maps displayed resilience to arrythmia. In conclusion, the proposed method enables saturation-recovery T1-mapping during systole, providing increased robustness against partial-voluming compared to diastolic imaging, for the benefit of T1-measurements in arrhythmic patients.
Gesehen am 24.07.2018
Die 1 ist im Titel tiefgestellt